PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. EDICO UTAMA, JAKARTA - Agus Sudradjat dan Dwi Susilowati (Fakultas Ekonomi Universitas Borobudur, 2015)
This study aims to examine and analyze the influence of leadership and work discipline on the performance of employees of PT. Edico Utama, Jakarta. Data collection through questionnaires distribution to 110 employees from 151 employees of PT. Edico Utama Jakarta. The method used in this sampling is purposive sampling method. Data analysis method used is multiple linear regression analysis. Based on the results of data analysis, the regression equation obtained is as follows: Y '= 9.930 + 0.355X1 + 0.524X2By using multiple regression analysis method, it can be concluded that simultaneously leadership and work discipline have positive and significant effect on employee performance with F value counted 307.563> F table = 3.08 at the real level α = 0.05, which means simultaneously leadership and work discipline influence positive and significant to the performance of employees of PT. Edico Utama, Jakarta. The value of coefficient of determination (R square) of 0.852. These results show that 85.2% of employee performance variables can be explained by independent variables, leadership and discipline work, while the rest of 14.8% by other variables not proposed in this study.Leadership variable (X1) and work discipline (X2) have positive and significant effect on employee performance (Y) with value 0,355 (X1) and 0.542 (X2). With t value equal to 15,092> t table = 1,659 at real level nayata α = 0,05. Thus it is known that partial leadership has a positive and significant influence on employee performance. There is a positive and partially significant influence between the variables of work discipline on employee performance. With t value counted 16,071> t table = 1,659 at nayata level α = 0,05. Keywords: Leadership, Work Discipline and Employee Performance.